Cell-cycle and apoptosis related and proteomics-based signaling pathways of human hepatoma Huh-7 cells treated by three currently used multi-RTK inhibitors - Xuejiao Ren; Xuejiao Ren; Qingning Zhang; Wenyan Guo; Lan Wang; Tao Wu; Wei Zhang; Ming Liu; Dezhi Kong (Frontiers Media S.A., 2022)
Sorafenib, lenvatinib and regorafenib, the multi-RTK inhibitors with potent anti-angiogenesis effects, are currently therapeutic drugs generally recommended for the patients with advanced hepatocellular carcinoma (HCC). To date, however, there have been no published studies on the mechanism underling differential effects of the three drugs on HCC cell proliferation, and the proteomic analysis in HCC cell lines treated by regorafenib or lenvatinib. The present study for the first time performed a direct comparison of the cell cycle arrest and apoptosis induction in the Huh-7 cells caused by sorafenib, regorafenib and lenvatinib at respective IC50 using flow cytometry technique, as well as their pharmacological interventions for influencing whole cell proteomics using tandem mass tag-based peptide-labeling coupled with the nLC-HRMS technique. Sorafenib, regorafenib and lenvatinib at respective IC50 drove the remaining surviving Huh-7 cells into a G0/G1 arrest, but lenvatinib and regorafenib were much more effective than sorafenib. Lenvatinib produced a much stronger induction of Huh-7 cells into early apoptosis than sorafenib and regorafenib, while necrotic cell proportion induced by regorafenib was 2.4 times as large as that by lenvatinib. The proteomic study revealed 419 proteins downregulated commonly by the three drugs at respective IC50. KEGG pathway analysis of the downregulated proteins indicated the ranking of top six signaling pathways including the spliceosome, DNA replication, cell cycle, mRNA surveillance, P53 and nucleotide excision repair involved in 33 proteins, all of which were directly related to their pharmacological effects on cell cycle and cell apoptosis. Notably, lenvatinib and regorafenib downregulated the proteins of PCNA, Cyclin B1, BCL-xL, TSP1, BUD31, SF3A1 and Mad2 much more strongly than sorafenib. Moreover, most of the proteins in the P53 signaling pathway were downregulated with lenvatinib and regorafenib by more than 36% at least. In conclusion, lenvatinib and regorafenib have much stronger potency against Huh-7 cell proliferation than sorafenib because of their more potent effects on cell cycle arrest and apoptosis induction. The underling mechanism may be at least due to the 33 downregulated proteins centralizing the signal pathways of cell cycle, p53 and DNA synthesis based on the present proteomics study.